THE EFFECTS OF AGRICULTURAL EXTENSION MATERIALS TO HUMAN RESOURCE OF FARMERS IN NAGARI PAKAN RABAA TENGAH KOTO PARIK GADANG DIATEH SUBDESHELF SOLOK SELATAN DISTICT - Voni, Sepsol; Hidayat, Rian; Malinda, Yola (Pendidikan Ekonomi, 2014)
ABSTRACTThe purpose of this study is to describe the effect of agricultural extension materials on human resource farmers in Nagari pakan rabaa tengah Koto Parik Gadang Diateh Subdeshelf Solok Selatan Distict. The Research used in this study is a case study. The population is all the groups farmer in many population 1.241 in Nagari Pakan Rabaa Tengah. Sampling was conducted with a sample of study respondents with a sample of 104 people consisting of four farmer groups. An analysis in this study is a 1. Descriptive analysis 2. Multiple linear regression f-test. The results of this study that : 1. Agricultural Materials significant and positive impact to improving the quality of human resources of technic farmers in Nagari Pakan Rabaa Tengah 2. The agricultural economics Materials significant and positive impact to improving the quality of human resource farmers in Nagari Pakan Rabaa Tengah 3. The management of farm households science significant and positive impact to improve the quality of human resources of farmers in Nagari Pakan Rabaa Tengah 4. To dynamics of farmers groups material significant and positive impact to improving the quality of human resources of farmers in Nagari Pakan Rabaa Tengah 5. The politics of agricultural development materials significant and positive impact on improving the quality of human resources of farmers in Nagari Pakan Rabaa Tengah 6. materials of agricultural technic, agricultural economics, management of farm households science, group dynamics and political development of agriculture science is collectively equally significant effect on improving the quality of human resources of farmers in Nagari Pakan Rabaa Tengah Koto Parik Gadang Diateh Subdeshelf Solok Selatan Distict. Â